2021
DOI: 10.1177/17562848211018654
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden and cost-effectiveness of therapies for Clostridiodes difficile infection: a narrative review

Abstract: Clostridioides difficile is the most common cause of healthcare-associated diarrhea. Disease complications as well as recurrent infections contribute significantly to morbidity and mortality. Over the past decades, there has been a rapid increase in the incidence of C. difficile infection (CDI), with a rise in the number of community-acquired cases. CDI has a profound economic impact on both the healthcare system and patients, secondary to recurrences, hospitalization, prolonged length of stay, cost of treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 99 publications
(144 reference statements)
2
15
0
2
Order By: Relevance
“…Findings from multivariable regression analysis in this study suggest it was fidaxomicin use more so than the overall treatment pathway that increased sustained response pre-post, further highlighting the important contribution of fidaxomicin. Reductions in recurrences and CDI readmissions post treatment pathway implementation demonstrate real-world experience consistent with prior literature, with the current study also Median of 5 days used for both due to non-significant difference [6 (4-10) vs. 4.5 (2-4.5), p = 0.251] c Equals savings from CDI-related readmission costs/the additional number of patients with sustained response d Equals savings from CDI-related readmission costs/the number of CDI-related readmissions avoided e Equals savings from CDI-related readmission costs/the number of bed-days saved providing a larger sample-size than available retrospective studies [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Findings from multivariable regression analysis in this study suggest it was fidaxomicin use more so than the overall treatment pathway that increased sustained response pre-post, further highlighting the important contribution of fidaxomicin. Reductions in recurrences and CDI readmissions post treatment pathway implementation demonstrate real-world experience consistent with prior literature, with the current study also Median of 5 days used for both due to non-significant difference [6 (4-10) vs. 4.5 (2-4.5), p = 0.251] c Equals savings from CDI-related readmission costs/the additional number of patients with sustained response d Equals savings from CDI-related readmission costs/the number of CDI-related readmissions avoided e Equals savings from CDI-related readmission costs/the number of bed-days saved providing a larger sample-size than available retrospective studies [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…A nasoduodenal tube was chosen for delivery, as it was indicated that the small intestine is the main source of bacterial translocation in AP ( 27 ). From the point of cost-effectiveness, FMT contributed to shortening of ICU stay by 2 days, and 5 days of hospitalisation might be important for saving medical costs and social costs ( 28 , 29 ). Further multi-centre studies are needed to confirm our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The only cost-effectiveness analysis is related to the comparison of the effect of fidaxomicin with standard therapy plus bezlotoxumab as reported by Lam et al focusing only on rCDI (237). Additionally, it is proven that fidaxomicin plus bezlotoxumab has similar effect to other SOC antibiotics (i.e., vancomycin or metronidazole) plus bezlotoxumab (42,238,239). Notably, pharmacoeconomic analyses demonstrate that standard therapy plus bezlotoxumab could be cost-effective compared with standard therapy alone, especially in preventing of rCDI episodes in those >65 years of age, those with severe CDI, and immunocompromised patients (234,237,(240)(241)(242)(243).…”
Section: Bezlotoxumab: the First Fda-approved Therapeutic Monoclonal ...mentioning
confidence: 99%